A selection of nitric oxide-releasing materials incorporating S-nitrosothiols - Lutzke, Alec, author; Reynolds, Melissa, advisor; Henry, Charles, committee member; Kennan, Alan, committee member; Kipper, Matthew, committee member (Colorado State University. Libraries, 2017)
Nitric oxide (NO) is a diatomic radical that occurs as a crucial component of mammalian biochemistry. As a signaling molecule, NO participates in the regulation of vascular tone and maintains the natural antithrombotic function of the healthy endothelium. Furthermore, NO is produced by phagocytes as part of the immune response, and exhibits both antimicrobial and wound-healing effects. In combination, these beneficial properties have led to the use of exogenous NO as a multifunctional therapeutic agent. However, the comparatively short half-life of NO under physiological conditions often renders systemic administration infeasible. This limitation is addressed by the use of NO-releasing polymeric materials, which permit the localized delivery of NO directly at the intended site of action. Such polymers have been utilized in the development of antithrombotic or antibacterial materials for biointerfacial applications, including tissue engineering and the fabrication of medical devices. NO release from polymers has most frequently been achieved through the incorporation of functional groups that are susceptible to NO-forming chemical decomposition in response to appropriate environmental stimuli. While numerous synthetic sources of NO are known, the S-nitrosothiol (RSNO) functional group occurs naturally in the form of S-nitrosocysteine residues in both proteins and small molecule species such as S-nitrosoglutathione. RSNOs are synthesized directly from thiol precursors, and their NO-forming decay has generally been established to produce the corresponding disulfide as a relatively benign organic byproduct. For these reasons, RSNOs have been conscripted as practical NO donors within a physiological environment. This dissertation describes the synthesis and characterization of RSNO-based NO-releasing polymers derived from the polysaccharides chitin and chitosan, as well as the development of amino acid ester-based NO-releasing biodegradable poly(organophosphazenes) (POPs). The broad use of chitin and chitosan in the development of materials for tissue engineering and wound treatment results in a significant overlap with the therapeutic properties of NO. NO-releasing derivatives of chitin and chitosan were prepared through partial substitution of the carbohydrate hydroxyl groups with the symmetrical dithiols 1,2-ethanedithiol, 1,3-propanedithiol, and 1,6-hexanedithiol, followed by S-nitrosation. Similarly, thiol-bearing polyphosphazenes were synthesized and used to produce NO-releasing variants. Polyphosphazenes are a unique polymer class possessing an inorganic backbone composed of alternating phosphorus and nitrogen atoms, and hydrolytically-sensitive POP derivatives with organic substituents have been prepared with distinctive physical and chemical properties. Although POPs have been evaluated as biomaterials, their potential as NO release platforms has not been previous explored. This work describes the development of NO-releasing biodegradable POPs derived from both the ethyl ester of L-cysteine and the 3-mercapto-3-methylbutyl ester of glycine. The NO release properties of all polymers were evaluated at physiological temperature and pH, and the results suggested potential suitability in future biomaterials applications.